A facile strategy to achieve high conduction and excellent chemical stability of lithium solid electrolytes. Issue 9 (23rd December 2014) - Song, Shufeng; Lu, Jia; Zheng, Feng; Duong, Hai M.; Lu, Li
Abstract : This research addresses the combination of high conductivity and excellent electrochemical stability in lithium solid electrolytes by halide doping. Abstract : Lithium solid electrolytes have shown their potential for high-energy density batteries. The use of solid electrolytes will also be able to overcome safety issues associated with conventional carbonate-based electrolytes. However, achieving the combination of high ionic conductivity and excellent electrochemical stability in lithium solid electrolytes is still a major challenge. Herein we report a facile strategy to achieve high conduction and excellent electrochemical stability by the substitution of Cl for O based on the concept of bottleneck size and binding energy. The ionic conductivities of Li10.42 Si1.5 P1.5 Cl0.08 O11.92 and Li10.42 Ge1.5 P1.5 Cl0.08 O11.92 are 1.03 × 10 −5 S cm −1 and 3.7 × 10 −5 S cm −1 at 27 °C, respectively, which are 13 orders of magnitude higher than that of the pure Li3 PO4, and 1 order of magnitude higher than that of the pristine Li10.5 Si1.5 P1.5 O12 . The electrochemical stability with metallic lithium is up to 9 V vs. Li + /Li, which is one of the widest electrochemical windows of solid electrolytes. This research also addresses the crystal structure, lithium ion migration mechanism, and battery performance.